2011
DOI: 10.1002/pbc.23367
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System: Role in Energy Regulation

Abstract: Cannabis sativa has been used since antiquity to treat many ailments, including eating disorders. The primary psychoactive constituent of this plant, Δ9-tetrahydrocannabinol (THC) is an FDA approved medication to treat nausea and emesis caused by cancer chemotherapeutic agents as well as to stimulate appetite in AIDS patients suffering from cachexia. The effects of THC are mediated through the endocannabinoid system (ECS), which promotes a positive energy balance through stimulation of appetite as well as shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 77 publications
0
23
0
1
Order By: Relevance
“…Nevertheless, Rivera's group attempted, for the first time, to investigate a functional link between the endocannabinoid system and cell proliferation in a model of diet-induced obesity ( 93 ) . The endocannabinoids, intracellular signalling lipid-related molecules, are well known to stimulate feeding ( 94 ) and, through in vitro work and the use of cannabinoid receptor knockout mice, had been known for some time to regulate neurogenesis in both the developing and adult nervous systems ( 95 99 ) . However, how the two phenomena are linked was unknown.…”
Section: Sfamentioning
confidence: 99%
“…Nevertheless, Rivera's group attempted, for the first time, to investigate a functional link between the endocannabinoid system and cell proliferation in a model of diet-induced obesity ( 93 ) . The endocannabinoids, intracellular signalling lipid-related molecules, are well known to stimulate feeding ( 94 ) and, through in vitro work and the use of cannabinoid receptor knockout mice, had been known for some time to regulate neurogenesis in both the developing and adult nervous systems ( 95 99 ) . However, how the two phenomena are linked was unknown.…”
Section: Sfamentioning
confidence: 99%
“…They are also overexpressed by immune competent cells of the brain following tissue injury, illness, and stress [150]. Cannabinoid receptors are activated by endogenous ligands, the endocannabinoids anandamide and 2-arachidonoylglycerol, which are biosynthesised locally during disruption of cell and tissue homeostasis, and act as autocrine [151] or paracrine [152] mediators to counteract such disruption [153][154][155]. CBD has very low affinity for CB1 and CB2 receptors, but inhibits anandamide inactivation, thus behaving as a weak 'indirect' CB1 and CB2 agonist.…”
Section: Spasticitymentioning
confidence: 99%
“…To date, it has been found that ECS is actively involved in control of several biological processes of pivotal importance in physiological and pathological conditions, such as memory and learning, mood, fear, food intake, immune response, and reproduction, neuroinflammatory and neurodegenerative diseases, anxiety, depression, immune deficiency, obesity, skin disorders, and fertility/infertility [76–82] .…”
Section: The Use Of Biological Network To Explore Cells Signalingmentioning
confidence: 99%